Understanding the Characteristics of Pig Butchering Scams: Impact on Victims and Challenges for Law Enforcement in Indonesia - Aissyach, Aissyach Noor Chairinovadanti; Sigid, Sigid Suseno; Budi, Budi Arta Atmaja (KRTHA BHAYANGKARA, 2025)
The pig butchering scam mode or "Sha Zhu Pan (杀猪盘), is a form of cyber-based investment fraud that is highly manipulative and has grown rapidly in Indonesia since the COVID-19 pandemic. This scam combines elements of romance and investment fraud (hybrid romance-investment scam) by building an emotional relationship and trust of the victim through social media or dating apps, before finally exploiting them to hand over funds to fake investment platforms. This study discusses the characteristics, schemes and tactics of pig butchering fraud, as well as the impact and challenges faced by law enforcement in dealing with this crime. The case study involved three fraud schemes that occurred in Indonesia: crypto investments, fake job postings, and romance scams, with significant losses ranging from hundreds of millions to billions of rupiah. The study found that low public understanding, limited law enforcement and the complexity of transnational networks are the main obstacles in eradicating this crime. Therefore, a more adaptive legal approach and an increase in people's digital literacy are needed to mitigate the impact of pig butchering fraud crimes in Indonesia.